2019
DOI: 10.3389/fmars.2019.00437
|View full text |Cite
|
Sign up to set email alerts
|

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level

Abstract: A major challenge for managing impacts and implementing effective mitigation measures and adaptation strategies for coastal zones affected by future sea level (SL) rise is our limited capacity to predict SL change at the coast on relevant spatial and temporal scales. Predicting coastal SL requires the ability to monitor and simulate a multitude of physical processes affecting SL, from local effects of wind waves and river runoff to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 204 publications
(231 reference statements)
1
43
0
Order By: Relevance
“…Models will inevitably perform well for some regions and timescales, but less well for others (e.g., Chepurin et al 2014;Becker et al 2016;Meyssignac et al 2017). In particular, models that are capable of reproducing coastal sea level variability observed to date will provide confidence in projecting future coastal sea level change (Ponte et al 2019). • Concerning our knowledge of tides at the coast, users of satellite altimetry in the deep ocean have grown accustomed to having reliable tide models that account for that dominant component of variability in their data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Models will inevitably perform well for some regions and timescales, but less well for others (e.g., Chepurin et al 2014;Becker et al 2016;Meyssignac et al 2017). In particular, models that are capable of reproducing coastal sea level variability observed to date will provide confidence in projecting future coastal sea level change (Ponte et al 2019). • Concerning our knowledge of tides at the coast, users of satellite altimetry in the deep ocean have grown accustomed to having reliable tide models that account for that dominant component of variability in their data.…”
Section: Discussionmentioning
confidence: 99%
“…Progress cannot be made with these and many other questions to do with sea level variability without access to the best, and most complete, observational and modelling data sets, as discussed further by Ponte et al (2019). One may note:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies found no correlation between river discharge and sea level variation, such as Blaha [15] for nonseasonal monthly records in the Chesapeake Bay (from tide gauge) or Han and Webster [16] for interannual sea level variability in the Bay of Bengal (based on simulations). Investigations on the importance of river discharges to coastal sea level variations have been made from hours to seasonal and interannual time scales [17]. Less attention has been brought on open ocean variations caused by river runoffs.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, its components should cover climate-observing parameters concerned with changes of the ocean circulation and its budgets of heat, freshwater, carbon, and nutrients, and the exchanges of heat, momentum, freshwater, and gases between the ocean, atmosphere, land, and cryosphere. Parameters concerned with sea level as an integral indicator for climate change (see also Ponte et al, 2019) should also be included. Several of the observing requirements are general in nature and concern the global ocean domain; others concern regional specificities and are presented separately in each ocean basin.…”
Section: Observing Requirements For Climatementioning
confidence: 99%